2013
DOI: 10.1007/978-1-4614-7783-9_11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antioxidants on Sperm Genetic Damage

Abstract: According to worldwide statistics, between one in four and one in five couples have fertility problems. These problems are equally distributed between males and females. Modern lifestyle has obviously increased these problems: endocrine-disrupting chemicals, such as plastic polymer catalysts, alkylphenols, phthalates and so on, and cosmetic additives seem to be strongly involved in this fertility problem. Many of these compounds increase oxidative stress (OS) and thus impair spermatogenesis. The oocyte has onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 71 publications
0
19
0
3
Order By: Relevance
“…The study shows that ginger powder in doses of 250 mg twice a day after 3 months is effective in reducing DNA fragmentation as compared with controls. This is the first direct demonstration of protective effect of ginger upon sperm DNA integrity in human although such an effect has previously been suggested with the use of other antioxidant (9, 23, 24). …”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The study shows that ginger powder in doses of 250 mg twice a day after 3 months is effective in reducing DNA fragmentation as compared with controls. This is the first direct demonstration of protective effect of ginger upon sperm DNA integrity in human although such an effect has previously been suggested with the use of other antioxidant (9, 23, 24). …”
Section: Discussionmentioning
confidence: 65%
“…Ginger also contains [6]-gingerol, 8-gingerol, 10-gingerol and 12-gingerol, which have similar anti-oxidate properties (27, 31). Animal modeling showed that ginger significantly lowered induced lipid peroxidation and amplified the levels of antioxidant enzymes, quantity and quality of sperm and plus serum glutathione (9, 16, 17, 32). …”
Section: Discussionmentioning
confidence: 99%
“…18 Approximately 20 percent of modern couples are infertile worldwide, and about half of these couples have suffered from male infertility. 19 Therefore, it is important to develop effective preventive strategies for male infertility. As shown in the above reports, scrotal hyperthermia can induce severe oxidative damage to spermatogenesis, but curcumin might have potent antioxidant activities in disease control of humans and animals.…”
Section: Introductionmentioning
confidence: 99%
“…In 1980, sperm DNA integrity was first presented as an independent fertility marker by Evenson et al . Although there is no yet a clear evidence of its clinical significance (Barratt & De Jonge, ), a number of studies have demonstrated that the proportion of sperm with fragmented DNA appears to be higher in infertile males compared with fertile controls (Agarwal & Said, ; Menezo et al ., ). Moreover, Perrin et al .…”
Section: Sperm Aneuploidy Predictive Factorsmentioning
confidence: 97%